Modified liquid diene rubber, rubber composition and sealing material
By using a specific modified liquid diene rubber, the problem of insufficient shear adhesion of the crosslinker of the existing rubber composition is solved, and the crosslinker with excellent adhesiveness is achieved, which is suitable for efficient bonding of sealing materials.
Patent Information
- Application Number
- CN202180034800.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-14
- Filing Date
- 2021-05-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-05-12
AI Technical Summary
The crosslinked material of the conventional rubber composition is not excellent enough, and it is difficult to effectively bond components of various materials when used as a sealing material.
A specific modified liquid diene rubber is used, which has a functional group derived from anhydride and contains more than 50% butadiene units. The weight average molecular weight converted by polystyrene is determined to be within the range of 5,000 to 50,000 by gel permeation chromatography.
A crosslinker with excellent adhesiveness evaluated by shear adhesion is achieved, and the adhesive properties of the rubber composition are improved, and it is suitable for the application of sealing materials.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The present invention relates to a modified liquid diene rubber, a rubber composition containing the modified liquid diene rubber, and a sealing material containing the rubber composition. Background Art
[0002] The rubber composition containing liquid rubber has excellent adhesiveness, and the crosslinked product obtained by crosslinking the liquid rubber has excellent adhesion to the adherend, etc. In addition, the modified liquid diene rubber modified with α, β-unsaturated carboxylic acid has a high affinity with polar materials such as metals, and the rubber composition containing the modified liquid diene rubber can be expected to have improved physical properties such as adhesion. For example, in the past, vulcanized products of rubber compositions containing diene rubber and modified liquid diene rubber modified with α, β-unsaturated carboxylic acid have been studied for tires and other rubber products (for example, see Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent document 1: Japanese Patent Application Laid-Open No. 59-006272. Summary of the invention
[0006] Problems to be solved by the invention
[0007] However, although the processability of conventional rubber compositions has been improved, the shear adhesion of their crosslinked products is not always excellent. In particular, when the composition is used as a sealing material, adhesion to components made of various materials is sought. The present invention is completed in view of the above actual situation, and provides a modified liquid diene rubber capable of obtaining a crosslinked product having excellent adhesion evaluated by shear adhesion, a rubber composition comprising the modified liquid diene rubber, and a sealing material obtained from the rubber composition.
[0008] Means used to solve problems
[0009] The present inventors have conducted intensive studies and have found that a specific modified liquid diene rubber can provide a cross-linked product having excellent adhesion as evaluated by shear adhesion, thereby completing the present invention.
[0010] That is, the present invention relates to the following [1] to
[11] .
[0011] [1] a modified liquid diene rubber (A) having a functional group (a) derived from an acid anhydride,
[0012] Containing 50% by mass or more of butadiene units relative to all monomer units,
[0013] When measured by gel permeation chromatography (GPC), the weight average molecular weight (Mw) in terms of polystyrene is in the range of 5,000 to 50,000.
[0014] [2] The modified liquid diene rubber (A) according to [1], wherein the modified liquid diene rubber (A) is a reaction product of a liquid diene rubber modified with an unsaturated carboxylic acid anhydride and a compound represented by the following chemical formula (2) or (3).
[0015]
[0016] (In the above formula (2), R a is a hydrogen atom or an optionally substituted alkyl group).
[0017]
[0018] (In the above formula (3), R b is a hydrogen atom or an optionally substituted alkyl group, and the presence of multiple R b Optional same or different).
[0019] [3] The modified liquid diene rubber (A) according to [1] or [2], wherein the weight average molecular weight (Mw) is in the range of 10,000 to 35,000.
[0020] [4] A rubber composition comprising the modified liquid diene rubber (A) according to any one of [1] to [3].
[0021] [5] The rubber composition according to [4], further comprising a solid rubber (B).
[0022] [6] The rubber composition according to [4] or [5], further comprising a filler.
[0023] [7] The rubber composition according to [6], wherein the filler contains calcium carbonate.
[0024] [8] The rubber composition according to any one of [4] to [7], further comprising a cross-linking agent.
[0025] [9] A sealing material obtained from the rubber composition according to any one of [4] to [8].
[0026]
[10] A cross-linked product obtained from the rubber composition according to any one of [4] to [8].
[0027]
[11] A sealing material obtained from the cross-linked product described in
[10] .
[0028] Effects of the Invention
[0029] According to the present invention, there are provided a modified liquid diene rubber capable of obtaining a crosslinked product having excellent adhesion as evaluated by shear adhesion, a rubber composition comprising the modified liquid diene rubber, and a sealing material obtained from the rubber composition. DETAILED DESCRIPTION
[0030] [Modified liquid diene rubber (A)]
[0031] The modified liquid diene rubber (A) of the present invention has a functional group (a) derived from an acid anhydride and contains 50% by mass or more of butadiene units based on all monomer units.
[0032] When measured by gel permeation chromatography (hereinafter also referred to as “GPC”), the weight average molecular weight (Mw) in terms of polystyrene is in the range of 5,000 to 50,000.
[0033] Such modified liquid diene rubber (A) and the rubber composition comprising the modified liquid diene rubber (A) are excellent in adhesion to other materials, for example, the shear adhesion of the cross-linked product of the rubber composition.
[0034] The modified liquid diene rubber (A) can be produced, for example, by adding a modifying compound corresponding to the functional group (a) derived from an acid anhydride to an unmodified liquid diene rubber (A′).
[0035] The unmodified liquid diene rubber (A') contains 50% or more of butadiene units relative to all monomer units constituting the polymer. The content of butadiene units is preferably 60 to 100% by mass, more preferably 70 to 100% by mass relative to all monomer units of the liquid diene rubber (A'). In addition, it is a preferred embodiment that the butadiene units contained in the liquid diene rubber (A') are 100% by mass (that is, all monomer units contained in the liquid diene rubber (A') are butadiene units).
[0036] Examples of other monomer units other than butadiene units that may be contained in the liquid diene rubber (A′) include conjugated diene (a1) units other than butadiene.
[0037] Examples of the conjugated diene (a1) include isoprene, 2,3-dimethylbutadiene, 2-phenylbutadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, 1,3-octadiene, 1,3-cyclohexadiene, 2-methyl-1,3-octadiene, 1,3,7-octatriene, myrcene, farnesene, and chloroprene. Among these conjugated dienes (a1), isoprene and farnesene are preferred.
[0038] The farnesene may be α-farnesene or β-farnesene represented by the following formula (1), and β-farnesene is preferred from the viewpoint of the ease of production of the liquid diene polymer (A). α-farnesene and β-farnesene may also be used in combination.
[0039] [Chemical formula 1]
[0040]
[0041] These conjugated dienes (a1) may be used alone or in combination of two or more.
[0042] The content of monomer units other than butadiene units in the unmodified liquid diene rubber (A′) is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less.
[0043] The vinyl content of the unmodified liquid diene rubber (A') is preferably 99 mol% or less, more preferably 90 mol% or less, further preferably 50 mol% or less, further preferably 20 mol% or less, and particularly preferably 10 mol% or less. In addition, the vinyl content of the unmodified liquid diene rubber (A') is preferably 1 mol% or more, more preferably 3 mol% or more, and further preferably 5 mol% or more. It should be noted that in the present invention, "vinyl content" refers to: the total molar % of conjugated diene units bonded by 1,2-bonds, 3,4-bonds (except for farnesene) and 3,13-bonds (in the case of farnesene)) in the total 100 mol% of conjugated diene units contained in the unmodified liquid diene rubber (A'). The vinyl content is expressed as follows: 1 H-NMR is calculated based on the area ratio of the peak attributed to the structural unit of the conjugated diene bonded via 1,2-bond, 3,4-bond (except farnesene) and 3,13-bond (in the case of farnesene) to the peak attributed to the structural unit of the conjugated diene bonded via 1,4-bond (except farnesene) and 1,13-bond (in the case of farnesene).
[0044] The unmodified liquid diene rubber (A') is preferably a polymer obtained by polymerizing butadiene and, if necessary, other monomers other than butadiene by, for example, emulsion polymerization or solution polymerization.
[0045] As the emulsion polymerization method, a known method or a method based on a known method can be applied. For example, a monomer containing a predetermined amount of a conjugated diene is emulsified and dispersed in the presence of an emulsifier, and emulsion polymerization is carried out using a radical polymerization initiator.
[0046] Examples of the emulsifier include long-chain fatty acid salts and rosin acid salts having at least 10 carbon atoms. Examples of the long-chain fatty acid salts include potassium or sodium salts of fatty acids such as capric acid, lauric acid, myristic acid, palmitic acid, oleic acid, and stearic acid.
[0047] As the dispersant, water is usually used, and a water-soluble organic solvent such as methanol or ethanol may be contained within a range that does not impair the stability during polymerization.
[0048] Examples of the radical polymerization initiator include persulfates such as ammonium persulfate and potassium persulfate; organic peroxides; and hydrogen peroxide.
[0049] In order to adjust the molecular weight of the obtained unmodified liquid diene rubber (A'), a chain transfer agent may be used. Examples of the chain transfer agent include mercaptans such as tert-dodecyl mercaptan and n-dodecyl mercaptan; carbon tetrachloride, thioglycolic acid, diterpene, terpinolene, γ-terpinene, α-methylstyrene dimer, and the like.
[0050] The temperature of the emulsion polymerization can be appropriately set depending on the type of radical polymerization initiator used, and is usually in the range of 0 to 100° C., preferably in the range of 0 to 60° C. The polymerization method may be either continuous polymerization or batch polymerization.
[0051] The polymerization reaction can be terminated by adding a polymerization terminator. Examples of the polymerization terminator include amine compounds such as isopropylhydroxylamine, diethylhydroxylamine, and hydroxylamine; quinone compounds such as hydroquinone and benzoquinone; and sodium nitrite.
[0052] After the polymerization reaction is terminated, an antioxidant can be added as needed. After the polymerization reaction is terminated, unreacted monomers are removed from the obtained latex as needed, then, using salts such as sodium chloride, calcium chloride, potassium chloride as coagulants, adding acids such as nitric acid and sulfuric acid as needed, while the pH of the coagulation system is adjusted to a specified value, while the above-mentioned unmodified liquid diene rubber (A') is coagulated, the dispersant is separated, and the unmodified liquid diene rubber (A') is thus recovered. Then, after washing and dehydration, drying is carried out to obtain the above-mentioned unmodified liquid diene rubber (A'). It should be noted that, when coagulating, the latex can be mixed with the filler oil made into an emulsified dispersion in advance as needed, and the unmodified liquid diene rubber (A') filled with oil is recovered in the form of.
[0053] As the solution polymerization method, a known method or a method based on a known method can be applied. For example, a monomer containing a conjugated diene is polymerized in a solvent using a Ziegler catalyst, a metallocene catalyst, an active metal or an active metal compound capable of anionic polymerization, and in the presence of a polar compound as required.
[0054] Examples of the solvent include aliphatic hydrocarbons such as n-butane, n-pentane, isopentane, n-hexane, n-heptane, and isooctane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; and aromatic hydrocarbons such as benzene, toluene, and xylene.
[0055] Examples of active metals capable of anionic polymerization include alkali metals such as lithium, sodium, and potassium; alkaline earth metals such as beryllium, magnesium, calcium, strontium, and barium; and lanthanide rare earth metals such as lanthanum and neodymium.
[0056] Among active metals capable of anionic polymerization, alkali metals and alkaline earth metals are preferred, and alkali metals are more preferred.
[0057] As the active metal compound capable of anionic polymerization, an organic alkali metal compound is preferred. Examples of the organic alkali metal compound include organic monolithium compounds such as methyl lithium, ethyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, hexyl lithium, phenyl lithium, stilbene lithium, etc.; polyfunctional organic lithium compounds such as dilithium methane, dilithium naphthalene, 1,4-dilithium butane, 1,4-dilithium-2-ethylcyclohexane, 1,3,5-trilithium benzene; sodium naphthalene, potassium naphthalene, etc. Among these organic alkali metal compounds, organic lithium compounds are preferred, and organic monolithium compounds are more preferred.
[0058] The amount of the organic alkali metal compound used can be appropriately set depending on the molecular weight, melt viscosity, etc. of the unmodified liquid diene rubber (A') and the modified liquid diene rubber (A), and is usually 0.01 to 3 parts by mass based on 100 parts by mass of all monomers including the conjugated diene.
[0059] The above-mentioned organic alkali metal compound may be reacted with a secondary amine such as dibutylamine, dihexylamine, dibenzylamine, etc. to be used in the form of an organic alkali metal amide.
[0060] Polar compounds usually do not deactivate the reaction in anionic polymerization and are used to adjust the microstructure of the conjugated diene site. Examples of polar compounds include ether compounds such as dibutyl ether, tetrahydrofuran, and ethylene glycol diethyl ether; tertiary amines such as tetramethylethylenediamine and trimethylamine; alkali metal alkoxides, phosphine compounds, etc. Polar compounds are usually used in an amount of 0.01 to 1000 moles relative to the organic alkali metal compound.
[0061] The temperature of solution polymerization is usually in the range of -80 to 150° C., preferably in the range of 0 to 100° C., and more preferably in the range of 10 to 90° C. The polymerization method may be either a batch method or a continuous method.
[0062] The polymerization reaction can be terminated by adding a polymerization terminator. Examples of the polymerization terminator include alcohols such as methanol and isopropanol. The unmodified liquid diene rubber (A') is separated by injecting the obtained polymerization reaction solution into a poor solvent such as methanol, or by washing the polymerization reaction solution with water, separating it, and then drying it, thereby separating the unmodified liquid diene rubber (A').
[0063] As a method for producing the unmodified liquid diene rubber (A'), among the above methods, a solution polymerization method is preferred.
[0064] The unmodified liquid diene rubber (A') is modified with a functional group (a) derived from an acid anhydride and used as a modified liquid diene rubber (A). Examples of the functional group derived from an acid anhydride include an acid anhydride group such as an unsaturated carboxylic acid anhydride group, an unsaturated carboxylic acid ester group derived from the acid anhydride group, an unsaturated carboxylic acid amide group, an unsaturated carboxylic acid imide group, and the like.
[0065] The method for producing the modified liquid diene rubber (A) is not particularly limited, and the modified liquid diene rubber (A) can be produced by, for example, a graft reaction of adding a compound corresponding to the functional group (a) derived from an acid anhydride as a modifying compound to the unmodified liquid diene rubber (A').
[0066] Examples of the compound corresponding to the unsaturated carboxylic anhydride group include unsaturated carboxylic anhydrides such as maleic anhydride and itaconic anhydride. Among these compounds, maleic anhydride is preferred.
[0067] Examples of the compound corresponding to the unsaturated carboxylic acid ester group include unsaturated carboxylic acid esters such as maleate, fumarate, itaconate, glycidyl (meth)acrylate, and hydroxyethyl (meth)acrylate.
[0068] Examples of the compound corresponding to the unsaturated carboxylic acid amide group include unsaturated carboxylic acid amides such as maleamide, fumaramide, and itaconamide.
[0069] Examples of the compound corresponding to the unsaturated carboxylic acid imide group include unsaturated carboxylic acid imides such as maleimide and itaconimide.
[0070] Among the modified liquid diene rubbers (A), preferred are: a modified liquid diene rubber (A1) modified with an unsaturated carboxylic acid anhydride obtained by adding an unsaturated carboxylic acid anhydride as a modifying compound to an unmodified liquid diene rubber (A'); a modified liquid diene rubber (A2) having an unsaturated carboxylic acid ester group obtained by further adding a compound having a hydroxyl group to the modified liquid diene rubber (A1); and a modified liquid diene rubber (A3) having an unsaturated carboxylic acid amide group obtained by further adding a compound having an amino group to the modified liquid diene rubber (A1), and preferred are the modified liquid diene rubber (A1) and the modified liquid diene rubber (A2).
[0071] The method for adding the modified compound to the unmodified liquid diene rubber (A') is not particularly limited. As such method, for example, a method of reacting the compound corresponding to the functional group (a) derived from the acid anhydride to the unmodified liquid diene rubber (A') can be cited. When the functional group (a) derived from the acid anhydride is an unsaturated carboxylic acid anhydride group, for example, a method of adding an unsaturated carboxylic acid anhydride and, as required, a free radical catalyst, and heating in the presence or absence of an organic solvent can be cited.
[0072] In general, the organic solvent used in the above method includes hydrocarbon solvents and halogenated hydrocarbon solvents. Among these organic solvents, hydrocarbon solvents such as n-butane, n-hexane, n-heptane, cyclohexane, benzene, toluene, and xylene are preferred.
[0073] In addition, examples of the radical catalyst used in the above method include di-sec-butyl peroxydicarbonate, tert-amyl peroxyvalerate, tert-amyl peroxy-2-ethylhexanoate, azobisisobutyronitrile, etc. Among these radical catalysts, azobisisobutyronitrile is preferred.
[0074] In addition, examples of the above-mentioned method include: a method of producing a modified liquid diene rubber (A2) having an unsaturated carboxylic acid ester group by further adding a compound having a hydroxyl group to the modified liquid diene rubber (A1) as described above after adding an unsaturated carboxylic acid anhydride to an unmodified liquid diene rubber (A') as described above to obtain a modified liquid diene rubber (A1) having an unsaturated carboxylic acid anhydride group; and a method of producing a modified liquid diene rubber (A3) having an unsaturated carboxylic acid amide group by further adding a compound having an amino group to the modified liquid diene rubber (A1).
[0075] As the compound having a hydroxyl group used in the production of the modified liquid diene rubber (A2), R a -OH(2) (in formula (2), R ais a hydrogen atom or an optionally substituted alkyl group), water or an alcohol, and more preferably an alcohol.
[0076] As the compound having an amino group used in the production of the modified liquid diene rubber (A3), R b 2-NH(3)(In formula (3), R b is a hydrogen atom or an optionally substituted alkyl group, and the presence of multiple R b (optionally the same or different) as shown in ammonia or amine.
[0077] When the modified liquid diene rubber (A) is a reaction product of a liquid diene rubber modified with an unsaturated carboxylic acid anhydride and a compound represented by the above chemical formula (2) or (3), especially an alcohol or a compound represented by the above chemical formula (3), the cross-linked product obtained from the rubber composition containing the reaction product tends to have better storage stability and better adhesion.
[0078] The detailed reasons for the excellent storage stability of the obtained cross-linked product are not yet clear, but it can be inferred that the reasons are as follows. When the modified liquid diene rubber (A1) having an unsaturated carboxylic acid anhydride group is stored in its original state, it sometimes reacts with water present in the air, for example, to form a modified liquid diene rubber having a functional group of a dicarboxylic acid structure with high polarity. It can be inferred that the modified liquid diene rubber having a functional group of a dicarboxylic acid structure has a strong interaction, which becomes the cause of the viscosity increase and the storage stability deteriorates. On the other hand, it can be inferred that when the modified liquid diene rubber (A1) having an unsaturated carboxylic acid anhydride group is reacted with an alcohol or a compound of (3), a dicarboxylic acid structure will not be formed, and the viscosity will not increase due to the strengthening of the above-mentioned interaction.
[0079] The compound represented by formula (2) is not particularly limited, but from the viewpoint of ease of modification reaction, an alcohol having 1 to 20 carbon atoms is preferred, a saturated alcohol having 1 to 20 carbon atoms is more preferred, methanol, ethanol, propanol, butanol, 3-methylbutanol is more preferred, and methanol and ethanol are still more preferred.
[0080] The compound represented by formula (3) is not particularly limited, and examples thereof include methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, sec-butylamine, tert-butylamine, n-pentylamine, n-hexylamine, n-heptylamine, n-octylamine, n-nonylamine, n-decylamine, n-undecylamine, n-dodecylamine (laurylamine), n-tridecylamine, n-tetradecylamine, n-pentadecylamine, n-hexadecylamine, n-heptadecylamine, n-octadecylamine (stearylamine), n-nonadecylamine, allylamine, oleylamine, benzylamine, cyclohexylamine, aniline, nitroaniline, aminophenol, aminobenzoic acid, anisidine, ethoxyphenylamine, monochloroaniline, dichloroaniline, toluidine, dimethylaniline, ethylaniline, and mixtures thereof such as coconut amine and tallow amine.
[0081] As the compound having a hydroxyl group and the compound having an amino group, only one kind may be used, or two or more kinds may be used.
[0082] The functional group equivalent of the functional group (a) derived from the acid anhydride of the modified liquid diene rubber (A) is preferably 1,200 to 7,600 g / eq, more preferably 1,400 to 4,000 g / eq, further preferably 1,700 to 3,100 g / eq, and further preferably 2,000 to 2,500 g / eq. By making the functional group equivalent of the functional group (a) derived from the acid anhydride of the modified liquid diene rubber (A) within the above range, the adhesiveness to other materials such as metals is excellent, and the handling property is also excellent. It should be noted that the functional group equivalent of the functional group (a) derived from the acid anhydride in this specification refers to the molecular weight per one functional group (a).
[0083] As a method for producing a modified liquid diene rubber (A) having a functional group equivalent of the functional group (a) within a specific range, it is effective to allow the reaction of the addition-modified compound to react at an appropriate reaction temperature and for a sufficient reaction time. For example, the temperature in the reaction of adding maleic anhydride to the unmodified liquid diene rubber (A') is preferably 100 to 200° C., more preferably 120 to 180° C. In addition, the reaction time is preferably 3 to 200 hours, more preferably 4 to 100 hours, and even more preferably 5 to 50 hours.
[0084] The functional group equivalent of the functional group (a) added to the modified liquid diene rubber (A) can be calculated from the addition reaction rate of the modified compound, or can be determined using various analytical instruments such as infrared spectroscopy and nuclear magnetic resonance spectroscopy.
[0085] The addition reaction rate of the modified compound of the modified liquid diene rubber (A) is preferably 40 to 100 mol%, more preferably 60 to 100 mol%, further preferably 80 to 100 mol%, and further preferably 90 to 100 mol%. If the addition reaction rate is within the above range, the residue of the modified compound or the low molecular compound derived from the modified compound in the obtained modified liquid diene rubber (A) becomes less, and therefore, the adverse effects derived from these compounds, such as adverse effects such as metal corrosion believed to be derived from acidic components such as maleic anhydride, can be further suppressed. The addition reaction rate of the modified compound can be obtained as follows: For example, when an unsaturated carboxylic acid or an unsaturated carboxylic anhydride is used as a modified compound, the amount of the unreacted modified compound is calculated by comparing the acid value of the sample after the modification reaction before and after cleaning, and thus obtained.
[0086] The amount of the modifying compound added to the modified liquid diene rubber (A) is not strictly limited, but from the viewpoint of fully exerting the characteristics of the obtained rubber composition, it is preferably in the range of 0.05 to 40 parts by mass, more preferably in the range of 0.1 to 30 parts by mass, further preferably in the range of 0.1 to 20 parts by mass, and further preferably in the range of 0.1 to 10 parts by mass relative to 100 parts by mass of the unmodified liquid diene rubber (A'). When the amount of the modifying compound added is more than 40 parts by mass, there is a tendency for the handling of the obtained modified liquid diene rubber (A) to become problematic, and when it is less than 0.05 parts by mass, there is a tendency for the adhesion to other materials, such as metals, to decrease.
[0087] The amount of the modifying compound added to the modified liquid diene rubber (A) can be calculated from the addition reaction rate of the modifying compound, or can be determined using various analytical instruments such as infrared spectroscopy and nuclear magnetic resonance spectroscopy.
[0088] In the modified liquid diene rubber (A), the position to introduce the functional group may be a polymerization terminal or a side chain of a polymer chain. In addition, the functional group may include one type alone or two or more types. Therefore, the modified liquid diene rubber (A) may be modified using one type of modifying compound or may be modified using two or more types of modifying compounds.
[0089] The weight average molecular weight (Mw) of the modified liquid diene rubber (A) is 5,000~50,000, preferably 6,000~40,000, more preferably 6,000~38,000, further preferably 9,000~36,000, and further preferably 10,000~35,000. If the Mw of the modified liquid diene rubber (A) is within the aforementioned range, the handling property is excellent, and the physical properties of the rubber composition containing the modified liquid diene rubber (A) are also excellent. In addition, if Mw exceeds the aforementioned upper limit value, there is a tendency for the viscosity to increase and the handling property to deteriorate. On the other hand, if Mw is less than the aforementioned lower limit value, there is a tendency that sufficient adhesion is not obtained. It should be noted that in the present invention, Mw is the number average molecular weight calculated based on polystyrene obtained by GPC measurement.
[0090] The molecular weight distribution (Mw / Mn) of the modified liquid diene rubber (A) is preferably 1.0 to 2.0, more preferably 1.0 to 1.5, further preferably 1.0 to 1.2, and further preferably 1.0 to 1.1. If Mw / Mn is within the above range, a composition having excellent handling properties of the modified liquid diene rubber at room temperature and little bleeding of low molecular weight components can be obtained. It should be noted that the molecular weight distribution (Mw / Mn) refers to the ratio of the weight average molecular weight (Mw) / number average molecular weight (Mn) calculated as polystyrene obtained by GPC measurement.
[0091] As a method for producing the modified liquid diene rubber (A) having such a specific molecular weight distribution, in addition to adding an antioxidant during the reaction of the addition modifying compound described later, there can be cited the following methods: purifying the unmodified liquid diene rubber (A') to fully remove the components that inhibit the reaction of the addition modifying compound. As a purification method, it is preferred to use washing with water or warm water, or an organic solvent represented by methanol, acetone, etc., or supercritical fluid carbon dioxide.
[0092] As a method for synthesizing the modified liquid diene rubber (A) having a specific molecular weight distribution, in addition to the above-mentioned washing, it is also effective to add an antioxidant during the reaction of adding the modifying compound. Preferred antioxidants used at this time include 2,6-di-tert-butyl-4-methylphenol (BHT), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol) (AO-40), 3,9-bis[1,1-dimethyl-2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane (AO-80), 2,4-bis[(octylthio)methyl]-6-methylphenol (Irganox 1520L), 2,4-bis[(dodecylthio)methyl]-6-methylphenol (Irganox 1726), 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate (Sumilizer GS), 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate (Sumilizer GM), 6-tert-butyl-4-[3-(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphinane-6-yloxy)propyl]-2-methylphenol (Sumilizer GP), tris(2,4-di-tert-butylphenyl) phosphite (Irgafos 168), 3,3'-dioctadecyl dithiodipropionate, hydroquinone, p-methoxyphenol, N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (Nokluck 6C), bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (LA-77Y), N,N-dioctadecylhydroxylamine (Irgastab FS 042), bis(4-tert-octylphenyl)amine (Irganox 5057), etc. Among these antioxidants, from the viewpoint of improving the storage stability of the obtained modified liquid diene rubber (A) (further suppressing the high molecular weight (typically, polymerization reaction)), N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (Nokluck 6C), N,N-dioctadecylhydroxylamine (Irgastab FS042), and bis(4-tert-octylphenyl)amine (Irganox 5057) as amine antioxidants are preferred, and N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (Nokluck 6C) is more preferred. In addition, the above antioxidants may be used alone or in combination of two or more.
[0093] The amount of the antioxidant added is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 3 parts by mass, based on 100 parts by mass of the unmodified liquid diene rubber (A') or the modified liquid diene rubber (A).
[0094] Furthermore, as a method for synthesizing a modified liquid diene rubber (A) having a specific molecular weight distribution, appropriate temperature management during the reaction of adding a modifying compound is also effective. For example, the temperature during the reaction of adding maleic anhydride to the unmodified liquid diene rubber (A') is preferably 100 to 200°C, more preferably 120 to 180°C.
[0095] The glass transition temperature (Tg) of the modified liquid diene rubber (A) may vary depending on the vinyl content of the conjugated diene unit, the type of conjugated diene, the content of units derived from monomers other than the conjugated diene, etc., and is preferably -100 to 30°C, more preferably -100 to 20°C, and further preferably -100 to 10°C. If Tg is within the above range, for example, the processability and adhesion of the rubber composition containing the modified liquid diene rubber (A) become good. In addition, the viscosity can be suppressed from increasing, and the handling is easy.
[0096] The modified liquid diene rubber (A) may be used alone or in combination of two or more.
[0097] The melt viscosity of the modified liquid diene rubber (A) measured at 38°C is preferably in the range of 3 to 400 Pa·s, more preferably in the range of 5 to 300 Pa·s, and further preferably in the range of 10 to 250 Pa·s. If the melt viscosity of the modified liquid diene rubber (A) at 38°C is within the aforementioned range, the handling properties of the modified liquid diene rubber (A) and its composition become good. It should be noted that in the present invention, the melt viscosity is a value measured using a Brookfield viscometer.
[0098] [Rubber composition]
[0099] The rubber composition of the present invention contains the above-mentioned modified liquid diene rubber (A) as a rubber component. The rubber composition of the present invention may contain components other than the modified liquid diene rubber (A).
[0100] [Crosslinking agent]
[0101] The rubber composition of the present invention may further contain a crosslinking agent in order to crosslink the rubber component including the modified liquid diene rubber (A). Examples of the crosslinking agent include sulfur, sulfur compounds, oxygen, organic peroxides, phenolic resins, amino resins, quinones and quinone dioxime derivatives, halogen compounds, aldehyde compounds, alcohol compounds, epoxy compounds, metal halides and organic metal halides, and silane compounds.
[0102] Examples of the sulfur compound include morpholine disulfide and alkylphenol disulfide.
[0103] Examples of the organic peroxide include cyclohexanone peroxide, methyl peracetoacetate, t-butyl peroxyisobutyrate, t-butyl peroxybenzoate, benzoyl peroxide, lauroyl peroxide, dicumyl peroxide, di-t-butyl peroxide, and 1,3-bis(t-butylperoxyisopropyl)benzene.
[0104] From the viewpoint of excellent corrosion resistance of the rubber composition of the present invention, organic peroxide is a preferred embodiment among these crosslinking agents. In the painting process of automobiles, etc., when crosslinking is performed using organic peroxide, corrosion to metals, plastics, etc. can be reduced.
[0105] These cross-linking agents may be used alone or in combination of two or more.
[0106] From the viewpoint of the mechanical properties of the crosslinked product, the content of the crosslinking agent is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.8 to 10 parts by mass based on 100 parts by mass of the rubber component including the modified liquid diene rubber (A).
[0107] In the rubber composition of the present invention, when sulfur, sulfur compounds, etc. are contained as a crosslinking agent for crosslinking (vulcanizing) the rubber, a vulcanization accelerator may be further contained. Examples of the vulcanization accelerator include guanidine compounds, sulfenamide compounds, thiazole compounds, thiuram compounds, thiourea compounds, dithiocarbamic acid compounds, aldehyde-amine compounds, aldehyde-amine compounds, imidazoline compounds, and xanthate compounds.
[0108] These vulcanization accelerators may be used alone or in combination of two or more.
[0109] The content of the vulcanization accelerator is preferably 0.1 to 15 parts by mass, more preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the rubber component including the modified liquid diene rubber (A).
[0110] In the rubber composition of the present invention, when sulfur, sulfur compounds, etc. are included as a crosslinking agent for crosslinking (vulcanization) the rubber, a vulcanization aid may be further included. Examples of the vulcanization aid include fatty acids such as stearic acid, metal oxides such as zinc white, and fatty acid metal salts such as zinc stearate.
[0111] These vulcanization aids may be used alone or in combination of two or more.
[0112] The content of the vulcanization aid is preferably 0.1 to 15 parts by mass, more preferably 0.5 to 10 parts by mass, based on the rubber component containing the modified liquid diene rubber (A).
[0113] [Solid rubber (B)]
[0114] The rubber composition of the present invention may contain solid rubber.
[0115] When the rubber composition of the present invention includes a modified liquid diene rubber (A) and a solid rubber (B), the rubber component is composed of the modified liquid diene rubber (A) and the following solid rubber (B). The rubber component can be composed of 1 to 99% by mass of the modified liquid diene rubber (A) and 99 to 1% by mass of the solid rubber (B), preferably composed of 1 to 95% by mass of the modified liquid diene rubber (A) and 99 to 5% by mass of the solid rubber (B), more preferably composed of 10 to 90% by mass of the modified liquid diene rubber (A) and 90 to 10% by mass of the solid rubber (B), and further preferably composed of 20 to 80% by mass of the modified liquid diene rubber (A) and 80 to 20% by mass of the solid rubber (B). By making the mixing ratio of the modified liquid diene rubber (A) and the solid rubber (B) within the above range, the breaking strength, elongation at break and adhesion of the rubber composition become good.
[0116] The solid rubber (B) used in the rubber composition of the present invention is a rubber that can be handled in a solid state at 20°C. The Mooney viscosity ML of the solid rubber (B) at 100°C is 1+4 The molecular weight of the solid rubber (B) is usually in the range of 20 to 200. Examples of the solid rubber (B) include natural rubber, polyisoprene rubber, polybutadiene rubber, styrene-butadiene copolymer rubber, styrene-isoprene copolymer rubber, acrylonitrile-butadiene copolymer rubber, chloroprene rubber, ethylene propylene rubber, and butyl rubber.
[0117] From the viewpoint of fully exerting the characteristics of the obtained rubber composition, the weight average molecular weight (Mw) of the solid rubber (B) is preferably 80,000 or more, more preferably within the range of 100,000 to 3,000,000.
[0118] Examples of the natural rubber include natural rubbers commonly used in the tire industry, such as SMR, SIR, TSR such as STR, and RSS, and modified natural rubbers such as high-purity natural rubber, epoxidized natural rubber, hydroxylated natural rubber, hydrogenated natural rubber, and grafted natural rubber. Among them, SMR20, STR20, and RSS#3 are preferred from the perspective of less quality deviation and ease of acquisition. These natural rubbers may be used alone or in combination of two or more.
[0119] As the above-mentioned polyisoprene rubber, for example, a Ziegler catalyst such as titanium tetrahalide-trialkylaluminum system, diethylaluminum chloride-cobalt system, trialkylaluminum-boron trifluoride-nickel system, diethylaluminum chloride-nickel system, etc.; a lanthanum rare earth metal catalyst such as triethylaluminum-organic acid neodymium-Lewis acid system, or a commercially available polyisoprene rubber obtained by polymerization using an organic alkali metal compound in the same manner as solution-polymerized styrene-butadiene copolymer rubber (hereinafter also referred to as S-SBR) can be used. The polyisoprene rubber obtained by polymerization using a Ziegler catalyst has a high cis-isomer content, so it is preferred. In addition, a polyisoprene rubber with an ultra-high cis-isomer content obtained using a lanthanum rare earth metal catalyst can be used.
[0120] The vinyl content of the polyisoprene rubber is preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less. If the vinyl content exceeds 50% by mass, the flexibility of the rubber composition at low temperatures tends to deteriorate. The lower limit of the vinyl content is not particularly limited. In addition, the glass transition temperature varies depending on the vinyl content, and is preferably -20°C or less, and more preferably -30°C or less.
[0121] The weight average molecular weight (Mw) of the polyisoprene rubber is preferably 90,000 to 2,000,000, more preferably 150,000 to 1,500,000. When Mw is within the above range, processability and mechanical strength are good.
[0122] The polyisoprene rubber may be partially provided with a branched structure or a polar functional group by using a multifunctional modifier such as tin tetrachloride, silicon tetrachloride, alkoxysilane having an epoxy group in the molecule, or alkoxysilane containing an amino group, as long as the effect of the present invention is not impaired.
[0123] As the above-mentioned polybutadiene rubber, for example, a Ziegler catalyst such as titanium tetrahalide-trialkylaluminum system, diethylaluminum chloride-cobalt system, trialkylaluminum-boron trifluoride-nickel system, diethylaluminum chloride-nickel system, or a lanthanum rare earth metal catalyst such as triethylaluminum-organic acid neodymium-Lewis acid system, or a commercially available polybutadiene rubber obtained by polymerization using an organic alkali metal compound in the same manner as S-SBR can be used. The polybutadiene rubber obtained by polymerization using a Ziegler catalyst has a high cis-isomer content, so it is preferred. In addition, a polybutadiene rubber with an ultra-high cis-isomer content obtained using a lanthanum rare earth metal catalyst can be used.
[0124] The vinyl content of the polybutadiene rubber is preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less. If the vinyl content exceeds 50% by mass, the flexibility of the rubber composition at low temperatures tends to deteriorate. The lower limit of the vinyl content is not particularly limited. In addition, the glass transition temperature varies depending on the vinyl content, and is preferably -40°C or less, and more preferably -50°C or less.
[0125] The weight average molecular weight (Mw) of the polybutadiene rubber is preferably 90,000 to 2,000,000, more preferably 150,000 to 1,500,000. When Mw is within the above range, processability and mechanical strength are good.
[0126] The polybutadiene rubber may be partially provided with a branched structure or a polar functional group by using a multifunctional modifier such as tin tetrachloride, silicon tetrachloride, alkoxysilane having an epoxy group in the molecule, or alkoxysilane containing an amino group, as long as the effect of the present invention is not impaired.
[0127] As styrene-butadiene copolymer rubber (hereinafter also referred to as SBR), appropriate rubber can be used according to the purpose, and specifically, the styrene content is preferably 0.1 to 70% by mass, more preferably 5 to 50% by mass, and further preferably 10 to 40% by mass. In addition, the vinyl content is preferably 0.1 to 60% by mass, and more preferably 0.1 to 55% by mass.
[0128] The weight average molecular weight (Mw) of SBR is preferably 100,000 to 2,500,000, more preferably 150,000 to 2,000,000, and even more preferably 200,000 to 1,500,000. When it is within the above range, both processability and mechanical strength can be achieved.
[0129] The glass transition temperature of the SBR used in the present invention, as determined by differential thermal analysis, is preferably -95 to 0° C., more preferably -95 to -5° C. By setting the glass transition temperature within the above range, an increase in viscosity can be suppressed, and handling can be facilitated.
[0130] The SBR that can be used in the present invention is obtained by copolymerizing styrene and butadiene. There is no particular limitation on the method for producing SBR, and emulsion polymerization, solution polymerization, gas phase polymerization, and bulk polymerization can all be used. Among these production methods, emulsion polymerization and solution polymerization are preferred.
[0131] Emulsion polymerized styrene-butadiene copolymer rubber (hereinafter also referred to as E-SBR) can be produced by a known or common emulsion polymerization method, for example, by emulsifying and dispersing a predetermined amount of styrene and butadiene monomers in the presence of an emulsifier and performing emulsion polymerization using a free radical polymerization initiator.
[0132] S-SBR can be produced by a common solution polymerization method, for example, by polymerizing styrene and butadiene in the presence of a polar compound as desired, using an active metal capable of anionic polymerization in a solvent.
[0133] Examples of the solvent include aliphatic hydrocarbons such as n-butane, n-pentane, isopentane, n-hexane, n-heptane, and isooctane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; and aromatic hydrocarbons such as benzene and toluene. These solvents are usually preferably used in a monomer concentration range of 1 to 50% by mass.
[0134] Examples of active metals capable of anionic polymerization include alkali metals such as lithium, sodium, and potassium; alkaline earth metals such as beryllium, magnesium, calcium, strontium, and barium; and lanthanide rare earth metals such as lanthanum and neodymium. Among these active metals, alkali metals and alkaline earth metals are preferred, and alkali metals are more preferred. Among alkali metals, organic alkali metal compounds are more preferred.
[0135] Examples of the organic alkali metal compound include organic monolithium compounds such as n-butyl lithium, sec-butyl lithium, tert-butyl lithium, hexyl lithium, phenyl lithium, and stilbene lithium; polyfunctional organic lithium compounds such as dilithium methane, 1,4-dilithium butane, 1,4-dilithium-2-ethylcyclohexane, and 1,3,5-trilithium benzene; sodium naphthalene, potassium naphthalene, and the like. Among them, organic lithium compounds are preferred, and organic monolithium compounds are more preferred. The amount of the organic alkali metal compound used is appropriately determined according to the desired molecular weight of the S-SBR.
[0136] The organic alkali metal compound can also be used in the form of an organic alkali metal amide by reacting with a secondary amine such as dibutylamine, dihexylamine, or dibenzylamine.
[0137] The polar compound is not particularly limited as long as it does not deactivate the reaction in anionic polymerization and is a compound commonly used to adjust the microstructure of the butadiene part and the distribution in the copolymer chain of styrene. Examples thereof include ether compounds such as dibutyl ether, tetrahydrofuran, and ethylene glycol diethyl ether; tertiary amines such as tetramethylethylenediamine and trimethylamine; alkali metal alkoxides, phosphine compounds, and the like.
[0138] The temperature of the polymerization reaction is usually in the range of -80 to 150° C., preferably 0 to 100° C., and more preferably 30 to 90° C. The polymerization method may be either a batch method or a continuous method. In order to improve the random copolymerization of styrene and butadiene, it is preferred to continuously or intermittently supply styrene and butadiene to the reaction solution in such a manner that the composition ratio of styrene to butadiene in the polymerization system is within a specific range.
[0139] The polymerization reaction can be terminated by adding an alcohol such as methanol or isopropanol as a polymerization terminator. The polymerization solution after the polymerization reaction is terminated can be directly dried, stripped, etc. to separate the solvent and recover the target S-SBR. It should be noted that before removing the solvent, the polymerization solution can be mixed with an extender oil in advance and recovered as an oil-filled rubber.
[0140] As the SBR, a modified SBR obtained by introducing a functional group into SBR may be used as long as the effects of the present invention are not impaired. Examples of the functional group include an amino group, an alkoxysilyl group, a hydroxyl group, an epoxy group, and a carboxyl group.
[0141] Examples of methods for producing modified SBR include, for example, a method in which, before adding a polymerization terminator, a coupling agent such as tin tetrachloride, tetrachlorosilane, dimethyldichlorosilane, dimethyldiethoxysilane, tetramethoxysilane, tetraethoxysilane, 3-aminopropyltriethoxysilane, tetraglycidyl-1,3-bisaminomethylcyclohexane, 2,4-toluene diisocyanate, or a polymerization terminal modifier such as 4,4'-bis(diethylamino)benzophenone or N-vinylpyrrolidone is added that reacts with the polymerization active terminal. Or other modifiers described in Japanese Patent Application Laid-Open No. 2011-132298 are added.
[0142] In the modified SBR, the position of the polymer into which the functional group is to be introduced may be the polymerization terminal or the side chain of the polymer chain.
[0143] As the styrene-isoprene copolymer rubber, acrylonitrile-butadiene copolymer rubber, chloroprene rubber, ethylene propylene rubber (EPM, EPDM, etc.), and butyl rubber, commercially available products can be used without particular limitation.
[0144] [filler]
[0145] The rubber composition of the present invention may contain fillers. Fillers refer to substances that are compounded for the purpose of improving mechanical strength, improving physical properties such as heat resistance or weather resistance, adjusting hardness, increasing the amount of rubber, etc. Examples of the fillers include calcium carbonate, calcium oxide, magnesium hydroxide, magnesium oxide, magnesium carbonate, aluminum hydroxide, barium sulfate, barium oxide, titanium oxide, iron oxide, zinc oxide, zinc carbonate, clays such as pagoda stone clay, kaolin clay, and calcined clay, mica, diatomaceous earth, carbon black, silica, glass fiber, carbon fiber, fibrous filler, glass beads, and other inorganic fillers; resin particles formed from resins such as cross-linked polyester, polystyrene, styrene-acrylic copolymer resin, or urea resin; synthetic fibers and natural fibers, etc.
[0146] It should be noted that when the filler is in a granular form, the shape of the particles can be various shapes such as spherical according to the desired physical properties. In addition, when the filler is in a granular form, it can be any of solid particles and hollow particles according to the desired physical properties, and can also be core-shell particles formed by various materials. In addition, these fillers can be surface treated with various compounds such as fatty acids, resin acids, fatty acid esters, and silane coupling agents.
[0147] Among these fillers, calcium carbonate, carbon black, and silica are preferred from the viewpoints of the reinforcing properties, price, and ease of handling of the obtained rubber composition and its cross-linked product, and calcium carbonate and carbon black are more preferred. These fillers may be used alone or in combination of two or more.
[0148] In the rubber composition of the present invention, the content of the filler is preferably 0.1 to 1500 parts by mass, more preferably 1 to 1300 parts by mass, further preferably 5 to 1000 parts by mass, and further preferably 10 to 800 parts by mass, relative to 100 parts by mass of the rubber component including the modified liquid diene rubber (A). When the content of the filler is within the above range, the processability and adhesiveness of the rubber composition are good.
[0149] [Oil]
[0150] The rubber composition of the present invention may contain oil. Oil refers to a substance added mainly to improve the processability of the rubber composition of the present invention, the dispersibility of other compounding agents, or to set the properties of the rubber composition to a desired range. Examples of the above-mentioned oil include mineral oil, vegetable oil, synthetic oil, etc.
[0151] Examples of mineral oils include paraffinic oils, cycloparaffinic oils, aromatic oils, etc. Examples of vegetable oils include castor oil, cottonseed oil, linseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, peanut oil, etc. Examples of synthetic oils include ethylene-α-olefin oligomers, liquid paraffin, etc.
[0152] Among these oils, paraffinic oils, naphthenic oils, and aromatic oils are preferred, and naphthenic oils are more preferred.
[0153] These oils may be used alone or in combination of two or more.
[0154] In the rubber composition of the present invention, the content of the oil is preferably 0.1 to 500 parts by mass, more preferably 1 to 450 parts by mass, further preferably 5 to 400 parts by mass, and further preferably 8 to 350 parts by mass, relative to 100 parts by mass of the rubber component including the modified liquid diene rubber (A). When the content of the oil is within the above range, the processability and adhesion of the rubber composition are good.
[0155] [Other ingredients]
[0156] The rubber composition of the present invention may contain a tackifier resin such as an aliphatic hydrocarbon resin, an alicyclic hydrocarbon resin, a C9 resin, a rosin resin, a coumarone-indene resin, or a phenolic resin as required for the purpose of improving processability, fluidity, etc., within a range not impairing the effects of the invention.
[0157] In addition, the rubber composition of the present invention may contain additives such as antioxidants, antioxidants, light stabilizers, anti-scorching agents, compounds containing functional groups, waxes, lubricants, plasticizers, processing aids, pigments, pigments, dyes, other colorants, flame retardants, antistatic agents, matting agents, anti-blocking agents, ultraviolet absorbers, release agents, foaming agents, antibacterial agents, antifungal agents, fragrances, dispersants, solvents, etc., as needed for the purpose of improving weather resistance, heat resistance, oxidation resistance, etc., within the range not impairing the effects of the present invention.
[0158] Examples of the antioxidant include hindered phenol compounds, phosphorus compounds, lactone compounds, and hydroxy compounds.
[0159] Examples of the antioxidant include amine-ketone compounds, imidazole compounds, amine compounds, phenol compounds, sulfur compounds, and phosphorus compounds.
[0160] In order to improve the adhesion and close fit between the rubber composition and the adherend, a compound containing a functional group may be added. As a compound containing a functional group, for example, alkoxysilane containing a functional group such as N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and γ-glycidoxypropyltrimethoxysilane; acrylates and methacrylates containing functional groups such as 2-hydroxyethyl acryloyl phosphate, 2-hydroxyethyl methacryloyl phosphate, nitrogen-containing acrylates, and nitrogen-containing methacrylates, etc. From the viewpoint of adhesion and close fit, epoxy group is a preferred embodiment as the above functional group.
[0161] Examples of the pigment include inorganic pigments such as titanium dioxide, zinc oxide, ultramarine blue, red iron, lithopone, lead, cadmium, iron, cobalt, aluminum, hydrochloride, and sulfate; and organic pigments such as azo pigments and copper phthalocyanine pigments.
[0162] Examples of the antistatic agent include hydrophilic compounds such as quaternary ammonium salts, polyglycols, and ethylene oxide derivatives.
[0163] Examples of the flame retardant include chloroalkyl phosphates, dimethyl methylphosphonate, bromine-phosphorus compounds, ammonium polyphosphate, neopentyl bromide-polyether, and brominated polyether. These additives may be used alone or in combination of two or more.
[0164] [Method for producing rubber composition]
[0165] The method for producing the rubber composition of the present invention is not particularly limited as long as the above-mentioned components can be uniformly mixed. The above-mentioned mixing can be carried out under normal pressure or in an air atmosphere. From the viewpoint of preventing bubbles from being mixed in the composition during mixing, it is preferably carried out under reduced pressure or in a nitrogen atmosphere. The rubber composition of the present invention obtained by uniformly dispersing the components in this way is preferably stored in a sealed container until use.
[0166] [Sealing material]
[0167] One suitable embodiment of the rubber composition of the present invention is to use it as a sealing material. In this case, one preferred embodiment is to use it as a cross-linked product as described below.
[0168] [Cross-linked products]
[0169] After the rubber composition of the present invention is applied to a substrate such as an oil-surface steel plate as required, a cross-linked product can be obtained by cross-linking it. The cross-linking conditions of the rubber composition can be appropriately set according to its use, and a cross-linked product can be produced by, for example, performing a cross-linking reaction at a temperature range of 130°C to 250°C for 10 minutes to 60 minutes. For example, when the rubber composition of the present invention is used in an automobile production line, after the rubber composition of the present invention is applied to the desired parts of various components (such as the gaps between the flanges of multiple frame components), it is baked and dried through the electroplating coating process of the vehicle body, and cross-linking is performed by the heat generated, thereby forming a cross-linked product at the desired part.
[0170] The cross-linked product obtained from the rubber composition of the present invention is excellent in adhesion evaluated by shear adhesion, and can be suitably used in, for example, automobile parts and the like. Example
[0171] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.
[0172] The components used in the present examples and comparative examples are shown below.
[0173] <Modified liquid diene rubber (A)>
[0174] The modified liquid diene rubber obtained in the following Preparation Examples 1 and 2 and Reference Preparation Examples 1 and 2 is
[0175] <Unmodified Liquid Diene Rubber (A')>
[0176] The unmodified liquid diene rubber obtained in Comparative Preparation Examples 1 and 2 described below
[0177] <Solid Rubber>
[0178] Butadiene rubber: "BR01" (manufactured by JSR Corporation), 1,4-cis bond content 95%, weight average molecular weight 520,000, Tg -103°C
[0179] <Crosslinking agent>
[0180] Dicumyl peroxide: "Parkmil D" (manufactured by NOF Corporation), 1 minute half-life temperature is 175°C
[0181] Sulfur: "Miukron OT-20" (Shikoku Chemical Industry Co., Ltd.)
[0182] <Vulcanization accelerator>
[0183] Stearic acid: "Lunec S-20" (manufactured by Kao Corporation)
[0184] Zinc oxide: Zinc white (manufactured by Sakai Chemical Industry Co., Ltd.)
[0185] <Vulcanization accelerator>
[0186] Vulcanization accelerator: "Nokusela NS" (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)
[0187] <Antioxidants>
[0188] Antioxidant: "Nokluck NS-6" (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)
[0189] <Packing>
[0190] Calcium carbonate: "Escalon #200" (manufactured by Sankyo Seikan Co., Ltd.), specific surface area: 11000cm 2 / g, the average particle size is 4.0 μm, and the apparent density is 0.42 g / mL.
[0191] Comparative Production Example 1: Liquid Polybutadiene (A'-1)
[0192] A fully dried pressure-resistant container is replaced with nitrogen, and 1000 g of hexane and 29 g of n-butyl lithium (1.6 mol / L hexane solution) are added to the pressure-resistant container. After the temperature is raised to 60°C, 1000 g of butadiene is added under stirring while the polymerization temperature is controlled to 60°C, and polymerization is carried out for 1 hour. Thereafter, methanol is added to terminate the polymerization reaction to obtain a polymerization solution. Water is added to the obtained polymerization reaction liquid and stirred, and the polymerization reaction liquid is washed with water. After the stirring is terminated and it is confirmed that the polymerization solution phase and the water phase have been separated, the water is separated. By drying the polymerization reaction liquid after washing at 70°C for 12 hours, a liquid polybutadiene (hereinafter also referred to as "polymer (A'-1)") as an unmodified liquid diene rubber is obtained. It should be noted that by 1 The vinyl content of the liquid polybutadiene (A'-1) determined by H-NMR measurement was 10%.
[0193] Comparative Production Example 2: Maleic Anhydride Modified Liquid Polyisoprene (α-1)
[0194] A fully dried pressure vessel is replaced with nitrogen, and 1200 g of cyclohexane and 320 g of sec-butyl lithium (1.06 mol / L hexane solution) are added to the pressure vessel. After the temperature is raised to 50°C, 1200 g of isoprene is added under stirring while controlling the polymerization temperature to 50°C, and polymerization is carried out for 1 hour. Thereafter, methanol is added to terminate the polymerization reaction to obtain a polymerization solution. Water is added to the obtained polymerization reaction liquid and stirred, and the polymerization reaction liquid is washed with water. After the stirring is terminated and it is confirmed that the polymerization solution phase and the aqueous phase have been separated, the water is separated. Liquid polyisoprene is obtained by drying the polymerization reaction liquid after washing at 70°C for 24 hours. It should be noted that by 1 The vinyl content of the liquid polyisoprene determined by H-NMR measurement is 7%. Next, 1.5 parts by mass of maleic anhydride and 0.1 parts by mass of BHT (2,6-di-tert-butyl-4-methylphenol, manufactured by Honshu Chemical Industry Co., Ltd.) are added to 100 parts by mass of the obtained polymer, and the mixture is reacted at 160°C for 20 hours to obtain maleic anhydride-modified polyisoprene (hereinafter also referred to as "polymer (α-1)"). It should be noted that the addition reaction rate of maleic anhydride determined by oxidation measurement is 99% or more, and the equivalent weight of the functional group (a) derived from the anhydride in the polymer (α-1) is 6,700 g / eq.
[0195] Preparation Example 1: Maleic anhydride-modified liquid polybutadiene (A-1)
[0196] 5 parts by mass of maleic anhydride and 0.1 parts by mass of Nocruk 6C (N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine, Ouchi Shinko Chemical Industry Co., Ltd.) were added to 100 parts by mass of the polymer (A'-1), and the mixture was reacted at 170°C for 24 hours to obtain maleic anhydride-modified liquid polybutadiene (A-1) (hereinafter also referred to as "polymer (A-1)"). It should be noted that the addition reaction rate of maleic anhydride determined by acid value titration was 95% or more, and the equivalent weight of the functional group (a) derived from the acid anhydride in the polymer (A-1) was 2,100 g / eq.
[0197] Preparation Example 2: Maleic anhydride-modified liquid polybutadiene methyl ester (A-2)
[0198] To the polymer (A-1), 1.05 molar equivalents of methanol were added relative to the added maleic anhydride groups, and the mixture was reacted at 90°C for 10 hours to obtain a maleic anhydride-modified liquid polybutadiene methyl ester (A-2) (hereinafter also referred to as "polymer (A-2)"). It should be noted that the reaction rate of the functional groups derived from maleic anhydride in the polymer (A-2) calculated from the infrared absorption spectrum was 100%.
[0199] Reference Production Example 1: Maleic Anhydride Modified Liquid Polybutadiene (A-3)
[0200] A fully dried pressure-resistant container is replaced with nitrogen, and 1800 g of cyclohexane and 210 g of sec-butyl lithium (1.06 mol / L hexane solution) are added to the pressure-resistant container. After the temperature is raised to 50°C, 960 g of butadiene is added under stirring while the polymerization temperature is controlled to 50°C, and polymerization is carried out for 1 hour. Thereafter, methanol is added to terminate the polymerization reaction to obtain a polymerization solution. Water is added to the obtained polymerization reaction liquid and stirred, and the polymerization reaction liquid is washed with water. After the stirring is terminated and it is confirmed that the polymerization solution phase and the water phase have been separated, the water is separated. Liquid polybutadiene is obtained by drying the polymerization reaction liquid after washing at 70°C for 12 hours. It should be noted that by 1 The vinyl content of the liquid polybutadiene determined by H-NMR measurement is 22%. Next, 8 parts by mass of maleic anhydride and 0.1 parts by mass of Nokluck 6C (N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine, Ouchi Shinko Chemical Industry Co., Ltd.) are added to 100 parts by mass of the obtained polymer, and the mixture is reacted at 160°C for 20 hours to obtain maleic anhydride-modified polybutadiene (hereinafter also referred to as "polymer (A-3)"). It should be noted that the addition reaction rate of maleic anhydride determined by oxidation measurement is 99% or more, and the equivalent weight of the functional group (a) derived from the anhydride in the polymer (A-3) is 1200 g / eq.
[0201] Reference Production Example 2: Maleic Anhydride Modified Liquid Polybutadiene Methyl Ester (A-4)
[0202] A fully dried pressure vessel is replaced with nitrogen, and 1000 g of hexane and 250 g of n-butyl lithium (1.6 mol / L hexane solution) are added to the pressure vessel. After the temperature is raised to 60°C, 1200 g of butadiene is added under stirring while the polymerization temperature is controlled to 50°C, and polymerization is carried out for 1 hour. Thereafter, methanol is added to terminate the polymerization reaction to obtain a polymerization solution. Water is added to the obtained polymerization reaction liquid and stirred, and the polymerization reaction liquid is washed with water. After the stirring is terminated and it is confirmed that the polymerization solution phase and the water phase have been separated, the water is separated. Liquid polybutadiene is obtained by drying the polymerization reaction liquid after washing at 70°C for 12 hours. It should be noted that by 1 The vinyl content of the liquid polybutadiene determined by H-NMR measurement is 11%. Next, 5 parts by mass of maleic anhydride and 0.1 parts by mass of Nokluck 6C (N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine, Ouchi Shinko Chemical Industry Co., Ltd.) are added to 100 parts by mass of the obtained polymer, and the reaction is carried out at 170°C for 24 hours to obtain maleic anhydride-modified liquid polybutadiene. It should be noted that the addition reaction rate of maleic anhydride determined by acid value titration is 95% or more, and the equivalent of the functional group (a) derived from the anhydride in the polymer is 2000 g / eq. Methanol is added in an amount of 1.05 molar equivalents relative to the added maleic anhydride group to the polymer, and the reaction is carried out at 90°C for 10 hours to obtain maleic anhydride-modified liquid polybutadiene methyl ester (A-4) (hereinafter also referred to as "polymer (A-4)"). The reaction rate of the functional groups derived from maleic anhydride in the polymer (A-4) calculated from the infrared absorption spectrum was 100%.
[0203] (Method for determining vinyl content)
[0204] A solution of 50 mg of the polymer obtained in the preparation example was dissolved in 1 mL of deuterated chloroform (CDCl3) and the mixture was analyzed using a 400 MHz 1 H-NMR was measured at a cumulative frequency of 512. From the spectrum obtained by the measurement, the vinyl content of each conjugated diene unit was determined by the following method.
[0205] (1) Vinyl content of butadiene units contained in the polymers obtained in the production examples, etc.
[0206] The mol % of the butadiene unit with 1,2-bond and the mol % of the vinyl cyclopentane unit (structural unit represented by formula (2)) were determined by the following method from the integral values of the following parts of the spectrum obtained by the above measurement. The sum of the mol % of the butadiene unit with 1,2-bond and the mol % of the vinyl cyclopentane unit was taken as the vinyl content.
[0207] [Chemical formula 2]
[0208]
[0209] 4.65~5.22ppm part: Part A (synthetic spectrum of butadiene units belonging to 1,2-bonds and structural units represented by formula (2))
[0210] 5.22~5.68ppm part: Part B (synthetic spectrum of 1,2-butadiene units and 1,4-butadiene units)
[0211] 5.68~5.95ppm portion: Part C (spectrum attributed to vinylcyclopentane unit)
[0212] Mole % of butadiene units with 1,2-bonds = [(integrated value of part A - integrated value of part B × 2) / 2] / [(integrated value of part A - integrated value of part C × 2) / 2+[integrated value of part C - (integrated value of part A - integrated value of part C × 2) / 2] / 2+integrated value of part C]×100
[0213] Mole % of vinyl cyclopentane unit = integrated value of part C / {(integrated value of part A - integrated value of part C × 2) / 2 + [integrated value of part C - (integrated value of part A - integrated value of part C × 2) / 2] / 2 + integrated value of part C} × 100
[0214] {Vinyl content (butadiene unit)} = mol% of 1,2-bond butadiene units + mol% of vinyl cyclopentane units.
[0215] (2) Vinyl content of isoprene units contained in the polymers obtained in the production examples, etc.
[0216] The vinyl content was determined by the following method from the integrated values of the following parts of the spectrum obtained by the above measurement.
[0217] 4.52~4.79ppm part: Part A' (synthetic spectrum of 3,4-bonded isoprene units)
[0218] 5.60~6.00ppm part: Part B' (synthetic spectrum of 1,2-bonded isoprene units)
[0219] 4.79~5.55ppm part: Part C' (synthetic spectrum of 1,4-bonded isoprene units)
[0220] {Vinyl content (isoprene unit)} = {(integrated value of part A' / 2) + (integrated value of part B')} / {(integrated value of part A' / 2) + integrated value of part B' + integrated value of part C'}
[0221] (Method for determining number average molecular weight (Mn), weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn))
[0222] The Mn and Mw of the polymers obtained in Preparation Examples 1 and 2, Reference Preparation Examples 1 and 2, and Comparative Preparation Examples 1 and 2 were determined by GPC (gel permeation chromatography) using standard polystyrene-equivalent molecular weights, and Mw / Mn was calculated based on these values. The measuring apparatus and conditions are as follows.
[0223] ・Equipment: GPC equipment "HLC-8320GPC" manufactured by Tosoh Corporation
[0224] ・Separation column: TSKgelSuperHZ4000 manufactured by Tosoh Corporation
[0225] ・Eluent: Tetrahydrofuran
[0226] ・Eluent flow rate: 0.7mL / min
[0227] ・Sample concentration: 5mg / 10mL
[0228] ・Column temperature: 40℃.
[0229] (Method for measuring melt viscosity)
[0230] The melt viscosity at 38° C. of the polymers obtained in Production Examples 1 and 2, Reference Production Examples 1 and 2, and Comparative Production Examples 1 and 2 was measured using a Brookfield viscometer (manufactured by BROOKFIELD ENGINEERING LABS. INC.).
[0231] (Glass transition temperature)
[0232] 10 mg of sample was placed in an aluminum baking tray, covered with an aluminum lid, and folded with a sample sealer. After cooling under the following conditions, a temperature spectrum was measured at a heating rate of 10°C / min using a differential scanning calorimeter (DSC), and the peak value of DSC was taken as the glass transition temperature (Tg). The measuring apparatus and conditions are as follows.
[0233] [Measurement apparatus and measurement conditions]
[0234] ・Equipment: Differential Scanning Calorimeter "DSC6200" manufactured by Seiko Instruments Co., Ltd.
[0235] ・Cooling device: Cooling controller manufactured by Seiko Instruments Co., Ltd.
[0236] ・Detection unit: Thermal flow rate type
[0237] ・Sample weight: 10mg
[0238] ・Cooling conditions: Cooling at a rate of 10°C / min to -130°C (then isothermally maintained at -130°C for 3 minutes)
[0239] ・Temperature increase condition: Temperature increase from -130℃ at 10℃ / min
[0240] ・Reference container: Aluminum
[0241] ・Reference weight: 0mg.
[0242] (Addition reaction rate)
[0243] To 3 g of the sample after the modification reaction, 180 mL of toluene and 20 mL of ethanol were added to dissolve the sample, and then neutralization titration was performed with a 0.1 N potassium hydroxide ethanol solution to determine the acid value.
[0244] Acid value (meq / g) = (AB) × F / S
[0245] A: Amount of 0.1N potassium hydroxide ethanol solution required for neutralization (mL)
[0246] B: Amount of 0.1N potassium hydroxide ethanol solution added when blank does not contain sample (mL)
[0247] F: Titer of 0.1N potassium hydroxide in ethanol
[0248] S: The mass of the sample weighed (g)
[0249] The sample after the modification reaction was washed with methanol 4 times (5 mL per 1 g of the sample) to remove unreacted maleic anhydride, and then dried under reduced pressure at 80°C for 12 hours, and the acid value was determined by the same method as above. The addition reaction rate of the modified compound was calculated according to the following formula.
[0250] [Addition reaction rate of modified compound (%)]=[acid value after washing (meq / g)] / [acid value before washing (meq / g)]×100.
[0251] (Functional group equivalent)
[0252] From the acid value after washing obtained above, the equivalent weight of the functional group (a) derived from the acid anhydride is calculated according to the following formula.
[0253] [Equivalent weight of the functional group (a) derived from the acid anhydride (g / eq)] = 1,000 / [acid value after washing (meq / g)].
[0254] (Reaction rate of anhydride group)
[0255] The reaction rate of the acid anhydride group when the compound represented by the chemical formula (2) or (3) is reacted with the acid anhydride-modified liquid diene rubber is calculated according to the following formula based on the infrared absorption spectra before and after the reaction measured using a Fourier transform infrared spectrophotometer FT / IR-4200 (manufactured by JASCO Corporation).
[0256] [Reaction rate of acid anhydride group (%)]=[1-(peak intensity ratio of functional groups derived from acid anhydride after reaction) / (peak intensity ratio of functional groups derived from acid anhydride before reaction)]×100.
[0257] It should be noted that when the acid anhydride used in the reaction is maleic anhydride, the peak derived from the C=O stretching of the unreacted product appears at 1781 cm -1 The intensity ratio of the peak to the peak derived from the main chain structure of the polymer which is unchanged before and after the reaction can be used.
[0258] [Table 1]
[0259]
[0260] (Examples 1-2 and Comparative Example 1)
[0261] The modified liquid diene rubber (A) or the unmodified liquid diene rubber (A') and the crosslinking agent were kneaded in the blending ratio (parts by mass) described in Table 2 to obtain a rubber composition. The obtained rubber composition was evaluated in the following manner. The results are shown in Table 2.
[0262] In addition, the measurement method of evaluation is as follows.
[0263] (Shear Adhesion)
[0264] The shear adhesion strength was measured in accordance with JIS K 6850. The test material was an SPCC steel plate specified in JIS G3141, and an article coated with a rust inhibitor and having a thickness of 1 mm was used. The rubber composition was applied to the above steel plate in a manner to a thickness of 0.15 mm, and then cross-linked at 150° C. for 40 minutes to prepare a sample, and the shear adhesion strength was measured. The tensile speed when measuring the shear adhesion strength was set to 5 mm / minute.
[0265] The numerical values of the respective Examples and Comparative Examples are relative values when the value of Comparative Example 1 is set to 100. It should be noted that the larger the numerical value, the better the shear adhesion of the rubber composition.
[0266] [Table 2]
[0267]
[0268] (Storage stability)
[0269] The modified liquid diene rubber (A) obtained in Preparation Examples 1 and 2 was left to stand in a constant temperature and humidity chamber at a temperature of 60° C. and a humidity of 50% rh for 12 days, and the change in melt viscosity over time was measured. The test results of the storage stability of the modified liquid diene rubber obtained in Preparation Example 1 are shown as Reference Example 1, and the test results of the storage stability of the modified liquid diene rubber obtained in Preparation Example 2 are shown as Example 3, and are shown in Table 3.
[0270] [Table 3]
[0271]
[0272] When comparing Examples 1 and 2 with Comparative Example 1, the use of the liquid diene rubber modified with an acid anhydride resulted in excellent adhesion to metal. When comparing Example 3 with Reference Example 1, the modified liquid diene rubber obtained by reacting the liquid rubber modified with an acid anhydride with alcohol had better storage stability.
[0273] (Examples 4-5 and Reference Examples 2-3)
[0274] The modified liquid diene rubber (A) and the crosslinking agent were kneaded in the blending ratios (parts by mass) shown in Table 4 to obtain a rubber composition. The obtained rubber composition was evaluated by the following method. The results are shown in Table 4.
[0275] In addition, the measurement method of evaluation is as follows.
[0276] (Adhesion Strength)
[0277] The shear adhesion was measured in accordance with JIS K 6850. The test material was an SPCC steel plate specified in JIS G3141, and a rust preventive-coated article with a thickness of 1 mm was used. The rubber composition was applied to the steel plate in a manner to a thickness of 0.2 mm, and then cross-linked at 180° C. for 30 minutes to prepare a cross-linked product, thereby preparing a sample and measuring the shear adhesion. The tensile speed when measuring the shear adhesion was set to 5 mm / minute.
[0278] The numerical values of the respective Examples and Reference Examples are relative values when the value of Reference Example 2 is set to 100. It should be noted that the larger the numerical value, the better the shear adhesion of the rubber composition.
[0279] [Table 4]
[0280]
[0281] Examples 4 and 5 were excellent in shear adhesion. In addition, even when compared with Reference Examples 2 and 3, these Examples were more excellent in shear adhesion than Reference Examples 2 and 3 because their weight average molecular weight (Mw) was 10,000 or more.
[0282] (Example 6 and Comparative Example 2)
[0283] The modified liquid diene rubber (A) or polymer (α-1), a crosslinking agent, a vulcanization aid and an antioxidant were kneaded in the blending ratios (parts by mass) listed in Table 5 to obtain a rubber composition. The obtained rubber composition was evaluated by the following method. The results are shown in Table 5.
[0284] In addition, the measurement method of evaluation is as follows.
[0285] (Heat resistance)
[0286] Heat resistance is evaluated by comparing the shear adhesion when the heating time is changed to 30 minutes and 90 minutes. The test material is an SPCC steel plate specified in JIS G3141, and an article coated with a rust inhibitor and having a thickness of 1 mm is used. After the rubber composition is applied to the above-mentioned steel plate in a thickness component of 0.2 mm, cross-linking and heat treatment are performed at 180°C and 30 minutes and 90 minutes to form a cross-linked product, thereby preparing a sample and measuring the shear adhesion. The determination of shear adhesion is carried out in accordance with JIS K 6850. The tensile speed when measuring the shear adhesion is set to 5 mm / minute.
[0287] The change in shear adhesive strength before and after heat treatment was calculated using the shear adhesive strength (I) after curing for 30 minutes and the shear adhesive strength (II) after heating for 90 minutes, using the calculation formula ((II)-(I)) / (I)×100.
[0288] [Table 5]
[0289]
[0290] When Example 6 is compared with Comparative Example 2, Example 6 in which the content of butadiene units in the modified liquid diene rubber (A) is 50% or more relative to all monomer units of the liquid diene rubber (A') does not decrease in adhesive strength before and after heat treatment and has excellent heat resistance.
[0291] (Example 7 and Reference Example 4)
[0292] The modified liquid diene rubber (A), the diene rubber and the filler were kneaded in the blending ratios (parts by mass) shown in Table 6 to obtain a rubber composition. The obtained rubber composition was evaluated by the following method. The results are shown in Table 6.
[0293] In addition, the measurement method of evaluation is as follows.
[0294] (Storage stability (2))
[0295] The rubber composition obtained in Example 7 or Reference Example 4 is placed in a constant temperature and humidity chamber at a temperature of 23°C and a humidity of 50% rh for 19 days, and the time-dependent change of the loss elastic modulus G" is measured. The loss elastic modulus G" is measured using a dynamic viscoelasticity measuring device ARES G2 manufactured by TA Instruments Co., Ltd. The composition is put into a cup with a bottom plate diameter of 40 mm in such a way that the thickness becomes 1 mm. A parallel plate with a diameter of 25 mm is used on the upper part. Under the conditions of a measuring temperature of 80°C and a strain of 0.1%, the measurement is performed while changing the frequency in the range of 0.1 Hz to 100 Hz, and the loss elastic modulus G" at 50 Hz is shown in Table 6.
[0296] [Table 6]
[0297]
[0298] When Example 7 is compared with Reference Example 4, the modified liquid diene rubber obtained by reacting the liquid rubber modified with an acid anhydride with an alcohol has more excellent storage stability.
[0299] (Examples 8-9 and Reference Examples 5-6)
[0300] The modified liquid diene rubber (A), the solid rubber (B), the unmodified liquid diene rubber (A'), the filler, the crosslinking agent and the antioxidant were kneaded according to the blending ratio (parts by mass) described in Table 7 to obtain a rubber composition. The obtained rubber composition was evaluated by the following method. The results are shown in Table 7.
[0301] In addition, the measurement method of evaluation is as follows.
[0302] (Adhesion Strength (2))
[0303] The shear adhesion was measured in accordance with JIS K 6850. The test material was an SPCC steel plate specified in JIS G3141, and a rust-inhibiting agent was applied to the steel plate with a thickness of 1 mm. The rubber composition was applied to the steel plate in a manner to a thickness of 0.2 mm, and then cross-linked at 175° C. for 30 minutes to prepare a cross-linked product, thereby preparing a sample and measuring the shear adhesion. The tensile speed when measuring the shear adhesion was set to 5 mm / minute.
[0304] The numerical values of the respective Examples and Reference Examples are relative values when the value of Reference Example 5 is set to 100. It should be noted that the larger the numerical value, the better the shear adhesion of the rubber composition.
[0305] [Table 7]
[0306]
[0307] Examples 8 and 9 were excellent in shear adhesive strength. Moreover, these examples were also excellent in shear adhesive strength compared with Reference Examples 5 and 6 because the weight average molecular weight (Mw) was 10,000 or more.
[0308] Industrial Applicability
[0309] The rubber composition containing the modified liquid diene rubber (A) having the functional group (a) derived from an acid anhydride obtained in the present invention has excellent handling properties and good adhesion as evaluated by shear adhesion, and therefore can be suitably used in sealing materials and is useful.
Claims
1. Use of a rubber composition comprising a modified liquid diene rubber (A), an unmodified liquid diene rubber (A'), calcium carbonate as a filler and a solid rubber (B) as a sealing material, wherein: The modified liquid diene rubber (A) has a functional group (a) derived from an acid anhydride, contains 50% by mass or more of butadiene units relative to all monomer units, and has a polystyrene-equivalent weight average molecular weight Mw in the range of 5,000 to 50,000 when measured by gel permeation chromatography GPC, The modified liquid diene rubber (A) is: a modified liquid diene rubber (A1) modified with an unsaturated carboxylic acid anhydride; or a modified liquid diene rubber (A2) having an unsaturated carboxylic acid ester group obtained by further adding a saturated alcohol having 1 to 20 carbon atoms to the modified liquid diene rubber (A1), When the modified liquid diene rubber (A) and the solid rubber (B) are used as the rubber component, the rubber component is 10 to 90 mass % of the modified liquid diene rubber (A) and 90 to 10 mass % of the solid rubber (B).
2. Use of a crosslinked product of a rubber composition comprising a modified liquid diene rubber (A), an unmodified liquid diene rubber (A'), calcium carbonate as a filler and a solid rubber (B) as a sealing material, wherein: The modified liquid diene rubber (A) has a functional group (a) derived from an acid anhydride, contains 50% by mass or more of butadiene units relative to all monomer units, and has a polystyrene-equivalent weight average molecular weight Mw in the range of 5,000 to 50,000 when measured by gel permeation chromatography GPC, The modified liquid diene rubber (A) is: a modified liquid diene rubber (A1) modified with an unsaturated carboxylic acid anhydride; or a modified liquid diene rubber (A2) having an unsaturated carboxylic acid ester group obtained by further adding a saturated alcohol having 1 to 20 carbon atoms to the modified liquid diene rubber (A1), When the modified liquid diene rubber (A) and the solid rubber (B) are used as the rubber component, the rubber component is 10 to 90 mass % of the modified liquid diene rubber (A) and 90 to 10 mass % of the solid rubber (B).
3. The use according to claim 1 or 2, wherein The weight average molecular weight Mw of the modified liquid diene rubber (A) is in the range of 10,000 to 35,000.
4. The use according to claim 1 or 2, wherein The rubber composition further includes a crosslinking agent.
Citation Information
Patent Citations
Adhesive composition and use
JP1984006272A
Modified copolymer and rubber composition and pneumatic tire using the same
JP2011132298A
Modified liquid diene-based rubber
CN111148767A
Rubber compositions
US20170073509A1
Modified liquid diene rubber and resin composition containing modified liquid diene rubber
US20180022835A1